Richard Salter sermons - Salter, Richard, 1721-1787.
Three manuscript sermons tipped into a single volume.
Pastor of the First Church of Christ, Mansfield, Conn.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: First Church of Christ (Mansfield, Conn.); Congregational churches -- Sermons -- Connecticut; Connecticut -- Church history; Mansfield (Conn.) -- History; Clergy